Research on High-speed Train Control System Based on Ethernet - Yan XIONG; He HUANG; Siyuan LI; Qing XU (机车电传动)
Because of the unique advantages of Ethernet in improving the efficiency of train maintenance, reducing maintenance costs and promoting train intellectualization, building intelligent control system based on Ethernet will be the development trend of train control. According to the current status of high-speed train control system, a train network control system based on Ethernet was proposed. Combining with the system topological structure, the system’s working efficiency, real-time performance and reliability were systematically expounded. The results showed that the system has good application prospects in the construction of high-speed train control system.